Cobalt in postharvest of gladiolus (Gladiolus grandiflorus Hort.) - Trejo-Téllez AnLibia Iris; Gómez-Merino Fernando Carlos; Gómez-Pérez Valeria; Castro-García Flor de Azalea (Revista Mexicana de Ciencias Agrícolas, 2018)
In this research, the effect of cobalt (Co) was evaluated in different concentrations (0, 0.3 and 0.6 mM) in variables postharvest of gladiola evaluated (Gladiolus grandif lorus Hort.) Cv. Borrega Roja. For seven days, we evaluated the water uptake through the f loral stems and the variation in their weight, as well as the kinetics of opening of the f lowers constituting each inf lorescence. After seven days of treatment, the weight of dry matter per organ (stem, leaves and inflorescence) and concentration was evaluated and N content per organ; concentration of chlorophyll a, b and total.Asignificant increase was observed in the water absorption in f lower stems treated with both concentrations of Co, compared with the control after 144 h after the start of the treatment; also in this sample, the lowest percentage of weight loss was recorded in fresh rods treated with 0.3 mM; however, this was not statistically different to other treatments. The low concentration of Co significantly increased N content in stems and leaf concentration of chlorophyll. Co had no influence on the kinetics of foliar opening and N concentration per organ. The total dry weights of leaves and stems were higher with the treatment of 0.3 mM Co.